Contribution to the study habits learning outcomes in senior high school - Debi Agustin; A. Muri Yusuf; Sufyarma (International Conferences on Educational, Social Sciences and Technology)
Results of study is a benchmark in view the success of student learning. The level of achievement of learning outcomes allegedly influenced by many factors. Study habits and is one of the factors suspected to affect learning outcomes. This study aimed to describe the contribution of the habit of learning on student learning outcomes. This study uses a quantitative approach a descriptive correlational. The study population 212, and a sample of 139 students obtained via technique. Proportional Random Sampling instruments used are instruments of learning habits, while the study results obtained from the value of student learning outcomes. Analysis of data using simple regression techniques. The research result shows that the habit of learning and learning outcomes at the high category. Contributions habit of learning to the learning outcomes 32.9%.